Nominal Group Technique (Ngt) Dan Aplikasinya Terhadap Pembinaan Elemen Etika Dan Nilai (Akhlak) Berasaskan Aktiviti Inkuiri - A Muqsith Ahmad; Zaharah Hussin; Farazila Yusof; Mohd Ridhuan Mohd Jamil (Politeknik & Kolej Komuniti Journal of Social Sciences and Humanities, 2017)
This study attempts to develop a set of elements for ethical and value-based activities inquiry model for engineering skills program in Skills Training Institute of Malaysia using Nominal Group Technique (NGT). It is critical as an effort towards plummeting social problems that afflict the young generation through the application of ethical and value-based activities in teaching and learning. This study was conducted in second phase (development phase) of researcher’s research based on expert’s consensus in identifying and accepting the elements of the model. The findings showed that the study has identified a total of 34 elements of ethics and values in the initial stage and finally, 30 elements of ethics and values is selected as a component in the development of model. In addition, the findings show that this technique has helped researchers get the data easily and quickly because of the construction of the model can be obtained directly through percentage score items tested based on experts consensus. Hence, NGT application has been a plus for the diversity of methods in research especially in Malaysia.